2016
DOI: 10.1352/1944-7558-121.5.383
|View full text |Cite
|
Sign up to set email alerts
|

Sibling Relationships in Adolescence and Early Adulthood With People Who Have Intellectual Disability

Abstract: Cross-sectional (N = 106) and longitudinal (N = 35) samples of siblings (ages 11-38) reported on closeness and conflict in their relationships with sisters and brothers with intellectual disability. For closeness, confirmatory factor analysis (CFA) distinguished feelings of emotional closeness from reciprocal sharing behaviors for these siblings. Age effects and changes over time indicated increasing emotional closeness and a general reduction in conflict from adolescence to young adulthood, with stable recipr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
1
15
0
1
Order By: Relevance
“…Similar to the findings in this study, prior researchers have reported that sibling constellation and demographic characteristics have relatively little influence on the sibling relationship when one sibling had ASD and/or IDD (Floyd, Costigan, & Richardson, 2016;Hodapp & Urbano, 2007). For example, using the same data set, but analyzing only the sibling closest in age to the brother or sister with ASD, we found that family size was not associated with positive affect in the sibling relationship .…”
Section: Discussionsupporting
confidence: 87%
“…Similar to the findings in this study, prior researchers have reported that sibling constellation and demographic characteristics have relatively little influence on the sibling relationship when one sibling had ASD and/or IDD (Floyd, Costigan, & Richardson, 2016;Hodapp & Urbano, 2007). For example, using the same data set, but analyzing only the sibling closest in age to the brother or sister with ASD, we found that family size was not associated with positive affect in the sibling relationship .…”
Section: Discussionsupporting
confidence: 87%
“…Since the uncertainty regarding the future situation of the person with ID is a concern of the siblings, a key issue is planning for the transition when caregiving passes from the parents to the siblings and under what circumstances they wish to assume that role (Heller & Arnold, 2010). Caregiving helps to build closer bonds between siblings; therefore, families and service systems should be conscious of this and acknowledge this fact (Floyd et al, 2016). Also, practices and policies should help siblings who are actual caregivers to attain a more balanced life, between the support given to the person with ID and their family and professional lives (Hodapp, Urbano, & Burke, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…One aspect that contributes to maintaining the closeness between siblings is the caregiving (Floyd, Costigan, & Richardson, 2016). Siblings of persons with ID support their brothers and sisters with a variety of emotional, physical, and practical assistance given throughout their lives (Hall & Rossetti, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent and young adult siblings of children with IDD (excluding ASD) who engaged in more caregiving reported more positive emotional bonds and reciprocal sharing with their brothers or sisters (Floyd et al, 2016). Levels of emotional closeness and reciprocal sharing were lowest in brothers who were younger than the individual with IDD, while sisters who lived with their siblings with IDD had the highest levels of reciprocal sharing (Floyd et al, 2016). Hostility toward the child with IDD was higher in families in which the child with IDD had more externalizing and total problems, greater parent-reported impact of IDD on the sibling, and higher parental stress (Shivers & Dykens, 2017).…”
Section: Sibling Relationship Quality and Family Functioning In Adole...mentioning
confidence: 99%